Ontogenetic and Spatiotemporal Changes in Isotopic Niche of Jumbo Squid (Dosidicus gigas) in the Southeastern Pacific - Hu, Guanyu; Boenish, Robert; Zhao, Zhenfang; Li, Jianhua; Chen, Xinjun (Frontiers in Marine Science, 2022)
Jumbo squid (Dosidicus gigas) plays an important role in food webs throughout the eastern Pacific; however, its trophic ecology is complex, because it is a highly migratory and opportunistic predator. In this study, δ13C and δ15N values were measured along the lateral wall of lower beak to investigate the ontogenetic and spatiotemporal feeding strategy shifts of jumbo squid, respectively. Both year and area had significant influences on δ13C (p < 0.01), while sex and stage had no significant influence on δ13C (p > 0.05). All explanatory variables (sex, stage, year, and area) had significant influences on δ15N (p < 0.05). The differences of niche among life stages indicated that the habitat and feeding habit were likely changed with the growth of individuals. Compared with normal years, the habitat of squids might change during the El Niño year. However, during the strong El Niño year, habitat location changed and niche size decreased compared to normal years. The trophic niche of D. gigas differed between different areas. Stable isotopes in early life stages were most effective for distinguishing different geographic populations. Females and males were likely to inhabit similar geographic areas throughout ontogeny. Unexpectedly, we found evidence to suggest females may have larger habitats and wider trophic niche than males. This study revealed the ontogenetic and spatiotemporal plasticity of habitat and feeding strategy of D. gigas.